Antiproliferative Effects and Phytochemical Characterization of ((Forssk) Vahl) and (Eckyl and Zeyh) Extracts - Carolyn Wanjira Muruthi PhD; Mathew Piero Ngugi PhD; Steven Maina Runo PhD; Peter Githaiga Mwitari PhD (SAGE Publishing, 2023)
Cancer mortality is a global concern. The current therapeutic approaches despite showing efficacy are characterized by several limitations. Search for alternatives has led to the use of herbal plants including C. edulis and P. capensis . However, there is limited research on antiproliferative effects of these medicinal plants. The study sought to evaluate antiproliferative effects of the plants against human breast and prostate cancers using cell viability, and gene expression assays to determine modulation of apoptotic genes. Further, Liquid Chromatography Mass Spectrophotometer (LC-MS) and Gas Chromatography Mass Spectrophotometer (GC-MS) analyses were performed to confirm phytocompounds in the extracts. The results indicated that ethylacetate extracts of C. edulis and P. capensis had the highest activity against cancer cells with IC 50 values of 2.12 ± 0.02, and 6.57 ± 0.03 μg/ml on HCC 1395 and 2.92 ± 0.17 and 5.00 ± 0.17 μg/ml on DU145, respectively. Moreover, the plants extracts exhibited relatively less cytotoxic activities against Vero cell lines (IC 50  > 20 μg/ml). The extracts also exhibit selectivity against the cancer cells (SI > 3). Further, mRNA expression of p53 in the treated HCC 1395 was increased by 7 and 3-fold, whereas by 3 and 2-fold in DU145 cells, upon treatment with ethylacetate extracts of C. edulis and P. capensis , respectively. Similarly, several-fold increases were observed in the number of transcripts of Bax in HCC 1395 and HOXB13 in DU145 cells. Phytochemical analyses detected presence of phytocompounds including flavonoids, phenolics, tocopherols and terpenoids which are associated with anticancer activity. Findings from this study provide a scientific validation for the folklore use of these plants in management of cancer.